Enhancing factor productivity of a greater yam + maize intercropping system under drip fertigation - M. Nedunchezhiyan; Kalidas Pati; V.B.S. Chauhan; S.K. Jata (JOURNAL OF ROOT CROPS, 2023)
Field experiments were conducted for consecutive two years (2015-16 and 2016-17) at the Regional Sation of ICAR-Central Tuber Crops Research Institute, Dumuduma, Bhubaneswar, Odisha to study the effect of drip irrigation and fertigation levels on factor productivity of a greater yam + maize intercropping. Drip irrigation treatments: I1=80% cumulative pan evaporation (CPE) during 1-270 days after planting (DAP); I2=100% of CPE during 1-90 DAP+80% of CPE during 91-270 DAP and I3=100% of CPE during 1-270 DAP were included in main plots. Fertigation treatments: F1=100-90-100 kg ha-1; F2=120-90-120 kg ha-1; F3=140-90-140 kg ha-1 and F4=160-90-160 kg ha-1 of N-P2O5-K2O were included in sub plots. A control (surface flood irrigation at 100% of CPE and soil application of N-P2O5-K2O 120-90-120 kg ha-1) was included to compare drip fertigation treatments. Treatment I3 resulted in maximum maize yield; I2 resulted in maximum greater yam and tuber equivalent yield (TEY). Fertigation at F4 was resulted in higher maize and greater yam yield and TEY than other treatments. Treatments I2F4 and I2F3 were on par and resulted in higher greater yam yield, TEY, nutrient and water use efficiency. The treatments control and I1F2 resulted in same level of TEY, which indicated saving of 0.684-0.710 million litre (17.9-25.9%) of water per ha under drip irrigation. Same level of TEY with the treatments viz., control and I2F1/I3F1 also indicated a saving of nutrients N-K2O 20-20 kg ha-1 (20%) under drip irrigation over soil application. The treatment I2F3 (drip irrigation at 100% of CPE during 1-90 DAP + 80% of CPE during 91-270 DAP along with fertigation of N-P2O5-K2O 140-90-140 kg ha-1) is recommended for greater yam + maize intercropping system considering greater TEY, nutrient and water use efficiency as well as minimum water requirement per kg of TEY production.